ANALISIS KURVA PHILIPS DI INDONESIA - Yogi Afriandi; Mike Triani (Universitas Negeri Padang, 2019)
This study aims to find out and analyze the factors that influence inflation in Indonesia in the Philips curve with variables that affect expected inflation, unemployment and world oil prices. This type of research is associative descriptive research, where the data used are secondary data from 1986 to 2017 obtained from institutions and related institutions, which are analyzed using the Ordinary Lest Square (OLS) method. Inflation that is expected to occur the same as the previous year's inflation has a significant effect on the positive direction of inflation in the Philips curve in Indonesia. Unemployment affects inflation with a significant positive effect on inflation in the Philips curve in Indonesia. World oil prices do not affect inflation with a positive but not significant the Philips curve in Indonesia, and expected inflation, unemployment, and world oil prices together have a significant effect on the Philips curve in Indonesia. The findings of this study indicate that inflation expected to occur the same as the previous year's inflation has a significant effect on the positive direction of inflation. Unemployment influences inflation with a significant positive effect on inflation. World oil prices do not affect inflation with a positive but not significant effect on the Philips curve in Indonesia , and expected inflation, unemployment, and world oil prices together have a significant effect on the Philips curve in Indonesia. Based on the results of this study, it is suggested that inflation is a measure of the economy of a country whether or not it is controlled by inflation, indicating that economy is also controlled in that country, the government should work together with the whole community so that people can be helped.